Tongue pressure and oral conditions affect volatile release from liquid systems in a model mouth - Benjamin, O.; Silcock, Patrick; Beauchamp, Jonathan; Büttner, Andrea; Everett, D. W. (Journal of Agricultural and Food Chemistry, 2012)
The release of volatile organic compounds (VOCs) into the mouth cavity is an integral part of the way flavor is perceived. An in vitro model mouth with an artificial tongue was developed to measure the dynamic release of VOCs from liquid model systems [e.g., aqueous solution, oil, and oil-in-water (O/W) emulsions] under oral conditions. The release of seven selected VOCs was affected by the different polarity and vapor pressure of the compounds and their affinity to the liquid system media. Different tongue pressure patterns were applied to the liquid systems, and the release of VOCs was monitored in real time using proton transfer reaction-mass spectrometry. The release was significantly more intense for longer tongue pressure duration and was influenced by the tongue altering the sample surface area and the distribution of the VOCs. The role of saliva (artificial versus human) and the sample temperature had a significant effect on VOC release. Saliva containing mucin and a higher sample temperature enhanced the release. © 2012 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.tongue
Keywords: model mouth; PTR-MS; saliva; sample temperature; tongue pressure; Volatile release